التأصيل الشرعي لفقه الأولويات : قضايا المرأة السياسية نموذجا - Zakiah Hanim Sarikon (al-Jami'ah al-Islamiyah al-'Alamiyah bi Maliziya, 2009)
This study attempts to establish a shariah framework for priorities-oriented jurisprudence with a special focus on the issues of women's involvement in politics. The research begins with the definition of priorities-oriented jurisprudence, and proceeds with the elaboration of the concept within the context of contemporary juristic ijtihad. It introduces a shariah framework for priorities-oriented jurisprudence, explains its major principles and its important role in dealing with contemporary issues. Of particular focus is the issue of women's political activity in terms of holding the top public office, voting right and represention in representative bodies such as the parliament and the local councils. As a means to establish a sound shariah ruling on these matters, references are made to scholarly discussions and argumentions of jurists by taking into accounts two elements. First, the contemporary developments that have taken place and secondly, the perspective of priorities-oriented jurisprudence. In terms of methodology, this study adopts two major methods: the deductive method and the comparative method. Based on these methods, the research has collected the available information regarding the differences of opinions among scholars in these matters and their various interpretations of evidence. From the application of this methodology, the study has come up with a number of views. The most important of which are that women are allowed to vote in the elections and to be representatives in parliament and other consultative councils, but not allowed, based on the principle of tarjih (selection of an opinion of greater profundity), to hold the post of prime minister or the elected head of state.